IMPLEMENTATION OF DISTANCE LEARNING MODELS IN INCREASING STUDENT LEARNING INDEPENDENCE IN MADRASAH ALIYAH NEGERI 1 JEMBER - Mashudi Mashudi (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2022)
The purpose of this study is to determine the independence of students' learning in distance learning at Madrasah Aliyah Negeri (MAN) Jember Regency. This research method uses a research method based on the philosophy of post positivism, which is used to examine the condition of natural objects. data source sampling was done purposively and snowballed. Data collection techniques with triangulation (combined), data analysis are inductive / qualitative, and the results of qualitative research emphasize meaning more than generalization. The research location is MAN 1 Jember, Jember Regency. The results of this study are in the form of educators at MAN 1 Jember are very dedicated in carrying out existing tasks. It can be seen that during distance learning during the pandemic, the board of educators still came to the school besides that by implementing strict health protocols. In its use, virtual learning brings students who are far away closer to continue learning and are not limited by time and space, but have not been able to be carried out due to existing technical constraints so that there is a need for readiness to use facilities and infrastructure. The conclusion in this study is the independence of student learning in distance learning at MAN 1 Jember in the form of learning activities that are given full flexibility over student learning activities with supervision within the scope of madrasahs. Flexibility is also given to students with the distribution of learning quotas that can be used to carry out student learning activities through room meeting applications such as Zoom meetings, google meet, Microsoft teams, WhatsApp Groups, Telegram, and so on. With the Covid-19 pandemic, it has not dampened the spirit of student learning independence and does not relax students' enthusiasm and learning outcomes